INTRAGROUP COOPERATION VS. INTRAGROUP COMPETITION: A Meta-Analytical Study - Ainun Na'im (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2004)
This study examines whether intragroup cooperation outperforms intragroup competition. Intragroup cooperation is a work setting when individuals in a group perceive that their goal attainments are positively related; while intragroup competition is a work setting when individuals in a group perceive that their goal attainments are negatively related. Performance is defined as group productivity level, speed of solving problems, and quality of the group outcomes.Meta-analytical method is used to test the hypothesis. The method combines and compares eight studies from various research disciplines i.e., education, psychology, organization, and business and accounting. The studies being analyzed also vary in terms of the research and experimental setting such as manufacturing operations and problem solving games.Meta-analytical study is relatively rare in Indonesia, so that this study is important to introduce and to show the importance and the benefit of the analysis for concluding a large number and different research in a similar domain of research question. In a simple term, a meta-analysis is a quantitative literature review. However, the analysis has a more powerful procedure (than the conventional literature review) to indicate more clearly, and in quantitative terms, the consistency, the differences and similarities of previous studies.The author found that intragroup cooperation outperforms intragroup competition is held across different experimental subject educational backgrounds such as education, psychology, and business and accounting. However, the extent of the difference in performance is higher in the subjects with psychology background than that of the subjects with business and accounting background. The reason is that business and accounting subjects are more exposed to competitive environments than those whose backgrounds are psychology and sociology.